FORMATISASI ONTOLOGI MANAJEMEN DAKWAH - ., Fahriansyah (Alhadharah: Jurnal Ilmu Dakwah, 2017)
When viewed in terms of elements of dawah combined with the ontology of general management, the study area of dawah management as a whole is 80 format. And when viewed in terms of the combination  of  dawah interaction with the ontology of general management, then obtained  96  formulation format, so that the total format of ontology of dawah management is 176 formulations ontology format.